Evaluasi Pengelolaan Dana Bos Di MTs NW Tampih Desa Rensing Kecamatan Sakra Barat Kabupaten Lombok Timur Tahun Pelajaran 2020/2021 - Warman, Budi; Samcandra, Lalu; Sukranudin, Sukranudin (FAKULTAS TARBIYAH, 2021)
This study aims to explain the program management process and to explain the implementation of the BOS program evaluation in MTs. NW Tampih This research was conducted in MTs. NW Tampih, Rensing Village, West Sakra District, East Lombok. This study descriptive qualitative approach. This research instrument uses interviews and documentation. The data sources are taken from the Principal and Treasurer of MTs NW Tampih. Data collection techniques are carried out through interviews and documentation. Data analysis is carried out by steps such as data reduction, data presentation, and conclusion drawing. data using Persistent Observation, triangulation, and using reference materials. The results showed that the management of BOS funds consisted of planning, distributing funds, taking funds, using funds, and reporting BOS funds in MTs. NW Tampih Rensing Village, Sakra Barat District has been running in accordance with applicable regulations, such as in school planning holding between school principals, teachers, school committees, and school guards to discuss what needs are needed by schools and teachers to support the learning process, Evaluation of BOS fund management at MTs. NW Tampih, Rensing Village, Sakra Barat Subdistrict, the evaluation of BOS fund management is the school principal whose evaluation is carried out quarterly to see plans that have been running according to the objectives of the BOS funds and the form of socialization provided by the school to parents of students, socialization of BOS funds is conveyed to parents of students if held only meeting with the guardians of students but the RKAS is also posted on the school wall so that it can be seen by the public, there is still a lack of socialization carried out by the school to parents of students, the school should hold outreach to parents of students specifically about the discussion of the BOS funds so that parents understand and understand about BOS funds